2013
DOI: 10.2478/cpe-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of HCl from Chloride Leach Solution of Spent HDS Catalyst by Solvent Extraction

Abstract: In the present work, amine based extractant and its mixture with cationic and solvating extractants were tested for the extraction of HCl from chloride solution containing Al(III). The chloride feed solution resulted from the leaching of spent HDS (hydro-desulfurization) catalysts. For this purpose, amine extractants, such as TOA (trioctyl amine), Alamine 336 (a mixture of tri-octyl/decyl amine), Alamine 308 (tri-isooctyl amine), and TEHA (tri 2-ethylhexyl amine) were used and the extraction and stripping beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Tertiary amines such as: Tri-n-dodecyl amine, tri-n-octylamine, Alamine 308 (tri-isooctylamine), TEHA (tri-2-ethyl hexyl amine), Alamine 336 (a mixture of triocty/decyl amine) have been proven to be effective extractant to recover HCl and H 2 SO 4 from aqueous solutions [5][6][7][8]. The extraction reaction of HCl by tertiary amines can be written as follows:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary amines such as: Tri-n-dodecyl amine, tri-n-octylamine, Alamine 308 (tri-isooctylamine), TEHA (tri-2-ethyl hexyl amine), Alamine 336 (a mixture of triocty/decyl amine) have been proven to be effective extractant to recover HCl and H 2 SO 4 from aqueous solutions [5][6][7][8]. The extraction reaction of HCl by tertiary amines can be written as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Banda et al [6] studied the extraction of HCl from chloride leach solution of hydro-disulfurization catalyst using trioctylamine, Alamine 330, Alamine 308 and TEHA. He found that stripping of HCl from the loaded extractant TEHA is easier when compared with other tested tertiary amines and a pure HCl was recovered.…”
mentioning
confidence: 99%
“…The extraction of HCl by tertiary amines is frequently assumed to be accompanied by the formation of an amine salt, which exists as an ion pair in the organic phase [17,35].…”
Section: Extraction Mechanismmentioning
confidence: 99%
“…Many studies have been reported on the recovery or the removal of mineral acids. High concentrations of mineral acids can be extracted using various extractants including Cyanex 923, tri-n-octylphosphine oxide, Alamine 336, Aliquat 336, trin-butyl phosphate (TBP), tris-(2-ethylhexyl) amine (TEHA), and Alamine 308 [12][13][14][15][16][17][18]. Often diluents are added to modify the physical properties (viscosity, specific gravity and surface tension) of the extractants and to cause different extraction complexes to form [19].…”
Section: Introductionmentioning
confidence: 99%
“…The extraction percentage of HCl decreased with the increase of HCl concentration in the feed. The solvent extraction reaction of HCl by TEHA (R 3 N) can be represented as 16,18) …”
Section: )mentioning
confidence: 99%